2019
DOI: 10.1029/2018jd030025
|View full text |Cite
|
Sign up to set email alerts
|

Total Basin Discharge From GRACE and Water Balance Method for the Yarlung Tsangpo River Basin, Southwestern China

Abstract: Total basin discharge plays an important role in the hydrological cycle for the regions. Estimation of total basin discharge cannot only help us manage water resources well but also provide a better understanding about water resources variability and hydrologic cycle. In this study, the Gravity Recovery and Climate Experiment (GRACE) data combined with precipitation and evapotranspiration (ET) is used to present first estimate of total basin discharge (~60.2 km3/year) based on water balance method over the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 75 publications
(112 reference statements)
1
19
0
Order By: Relevance
“…Comparing with single decision trees, the RF and XGB could reduce overfitting and improve accuracy because of their ensemble (bagging and boosting) techniques. And comparing with the ANN-based model that was used for estimating total basin discharge time series in recent publication (Xie et al, 2019), the models presented in this study are able to reconstruct the spatial patterns of the TWSA instead of one-dimensional time series by introducing geolocations as variables and training the models at grids scale. In addition, variable importance can be quantified in the RF and XBG model, providing an insight into the variables' significance to the TWSA estimations.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with single decision trees, the RF and XGB could reduce overfitting and improve accuracy because of their ensemble (bagging and boosting) techniques. And comparing with the ANN-based model that was used for estimating total basin discharge time series in recent publication (Xie et al, 2019), the models presented in this study are able to reconstruct the spatial patterns of the TWSA instead of one-dimensional time series by introducing geolocations as variables and training the models at grids scale. In addition, variable importance can be quantified in the RF and XBG model, providing an insight into the variables' significance to the TWSA estimations.…”
Section: Discussionmentioning
confidence: 99%
“…Effective discharge monitoring is important for water management and utilization, as well as the scientific development of dispatch plans [26][27][28]. However, due to the variation in regional precipitation frequency and intensity, the estimation of discharge remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Dinh and Fllipe [38] found that water volume change evaluated from GRACE TWSA was highly correlated to river discharge with correlations ranging from 0.77 to 0.88 over the Amazon River Basin. Chen et al [39] and Xie et al [40] also declared that TWSA data from GRACE satellites were essential to estimate discharge at a monthly and seasonal time scale, by comparing with simulations and in situ measurements. Based on the fact that the above-mentioned studies merely focused on single data sources, the combination of Jason-2/3 altimetry satellites and the GRACE mission in this study will greatly improve the discharge estimation.…”
Section: Introductionmentioning
confidence: 99%